(untitled) (Community Based Medical Journal, 2025)
Vaccination is one of the important preventive measures against morbidity and mortality related to the COVID-19 infection. This cross-sectional, descriptive study was conducted among patients attending outpatient departments (OPD) at Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between March and April of 2022, to determine vaccination coverage and knowledge on COVID-19 infection. We adopted a purposive sampling technique. Data were collected on a pre-designed questionnaire by direct interviewing a total of 150 patients attending at OPD. Respondents’ age, sex, occupation, family living and income status, vaccination related data and knowledge level on chain of infection were inquired and recorded on the data sheet. Age of the respondents ranged between 20 and 65 years; mean age was 36.37±11.088 years. 82 were males and 68 were females (male-female ratio was 1.2:1). The majority of respondents were Muslim (95.3%), literate (87.33%), hailing from middle class family (61.33%), and married (78.67%). 33.33% had signs and symptoms suggestive of COVID-19 infection. Corona tests were adopted by 31.33%, 24.67% revealed COVID test positive. 16% was on isolation and 20% received hospital based treatment. 90% of the respondents got vaccinated; 87.33% were fully immunized and 2.67% were partially immunized. Causes for declining vaccine were – do not like, not interested (4.67%) and afraid of complications (5.33%). Correct knowledge of causative agent of COVID-19 as a virus (98.67%), animal reservoir (98.67%), human reservoir (98.67%), source of infection (100%), portal of exit (100%) and susceptible host (100%) were excellent. Correct knowledge mode of transmission as droplet infection (76%) and portal of entry (60.67%) were good. CBMJ 2025 January: Vol. 14 No. 01 P: 85-88